Здійснення процесу книгообміну у Науковій бібліотеці Харківського державного університету харчування та торгівлі - Бакуменко, Л. Г. (Видавництво Львівської політехніки, 2015)
Розглянуто питання формування фондів через впровадження процесів книгообміну в роботу наукової бібліотеки ХДУХТ шляхом створення сектору обмінного фонду та посилення зв’язків з іншими бібліотечними закладами за допомогою книгообміну. This article considers issues of formation of book collections through implementation of book exchange processes in work of Kharkiv State University of Food Technology and Trade Scientific Library. It was realised via creation of book exchange subdivision and strengthening contacts with other library institutions regarding book exchange.
Strengthening relations between Scientific Library of Kharkiv state university of food technology and trade and other libraries through book exchange
Keywords: книгообмін; бібліотечні заклади; міжбібліотечна взаємодія; book exchange; libraries; interlibrary interaction